Exploring Interactive Online Script Creation as a Novel Assessment Method in Higher Education - Baumeister, Tobias; Hofmann, Sascha; Kob, Thomas; Fey, Dietmar (Education and New Developments 2024, 2024)
This study presents a new assessment approach wherein students collaboratively develop interactive online scripts (text enriched by images, videos, and self-assessment quizzes) on course contents throughout the semester. The aim is for students to become subject matter experts, ensuring that the content is comprehensible for their peers. This method offers several advantages, including rapid integration of new contents into course material without a heavy workload for lecturers, who only need to produce in-class materials rather than exhaustive study guides. Moreover, students acquire valuable competencies and soft skills such as structuring of learning material as well as collaborative learning. It also aims to foster self-reflection on effective learning strategies. Results from a voluntary survey indicate that 17 out of 18 students found script creation beneficial for deepening their understanding of course contents. However, evaluation in a course of 57 participants yielded mixed results, with both exemplary and substandard submissions. The substandard results are difficult to deal with, as students then have no study material for these topics. Notable challenges include unclear assignment requirements, ineffective group dynamics, and a time-intensive nature of student tutoring by teaching assistants. Furthermore, despite defined assessment criteria, assessing script quality proved challenging due to strong homogeneity among submissions. Addressing these challenges requires enhanced training for teaching assistants providing feedback to the students, and strategies for managing gaps in script coverage. This study underscores the need for competent supervision and ongoing refinement of this assessment process to optimize learning outcomes in higher education settings.<br
Keywords: Assessment; cooperative learning; online learning